Lifetime leisure music exposure associated with increased frequency of tinnitus - Moore, David R.; Zobay, Oliver; Mackinnon, Robert C.; Whitmer, William M.; Akeroyd, Michael A. (Elsevier, 2017)
Tinnitus has been linked to noise exposure, a common form of which is listening to music as a leisure activity. The relationship between tinnitus and type and duration of music exposure is not well understood. We conducted an internet-based population study that asked participants questions about lifetime music exposure and hearing, and included a hearing test involving speech intelligibility in noise, the High Frequency Digit Triplets Test. 4950 people aged 17 – 75 years completed all questions and the hearing test. Results were analyzed using multinomial regression models. High exposure to leisure music, hearing difficulty, increasing age and workplace noise exposure were independently associated with increased tinnitus. Three forms of music exposure (pubs/clubs, concerts, personal music players) did not differ in their relationship to tinnitus. More males than females reported tinnitus. The objective measure of speech reception threshold had only a minimal relationship with tinnitus. Self-reported hearing difficulty was more strongly associated with tinnitus, but 76% of people reporting usual or constant tinnitus also reported little or no hearing difficulty. Overall, around 40% of participants of all ages reported never experiencing tinnitus, while 29% reported sometimes, usually or constantly experiencing tinnitus that lasted more than 5 minutes. Together, the results suggest that tinnitus is much more common than hearing loss, but that there is little association between the two, especially among the younger adults disproportionately sampled in this study.